Enhanced storage ability by using a porous pyrrhotite@N-doped carbon yolk–shell structure as an advanced anode material for sodium-ion batteries. Issue 41 (9th October 2018) - Veerasubramani, Ganesh Kumar; Subramanian, Yuvaraj; Park, Myung-Soo; Nagaraju, Goli; Senthilkumar, Baskar; Lee, Yun-Sung; Kim, Dong-Won
Abstract : The yolk–shell structured Fe1− x S encapsulated by N-doped carbon exhibited high discharge capacity, good cycling stability and excellent rate capability. Abstract : Sodium-ion batteries (SIBs) are undoubtedly the most promising alternatives to lithium-ion batteries considering the natural abundance, distribution and cost of sodium resources. Still, SIBs face challenges in the development of suitable anode materials due to the large volume change during sodiation/de-sodiation, which results in inferior cycling stability. Herein, we synthesized a yolk–shell structured pyrrhotite (Fe1− x S)@N-doped carbon (FS@NC) through a solution-based method and investigated its electrochemical properties for use in SIBs as an anode material. The optimized yolk–shell structured FS@NC with distinctive voids and a core exhibited a high reversible capacity of 594 mA h g −1 over 100 cycles at 100 mA g −1, excellent rate capability and superior cycling performance compared to core–shell and pristine Fe1− x S materials. During the charge and discharge cycles, the synergistic effect of the porous core (Fe1− x S) with empty voids and a defective carbon shell configuration provided a large electrode/electrolyte contact area and shortened the diffusion path for electrons and sodium ions. It also mitigated the structural degradation by accommodating the volume change during continuous cycles, which was confirmed by ex situ SEM and TEM analyses. To demonstrate a practical application, we assembled a sodium-ion full cell with an O3-type NaCo0.5 Fe0.5 O2 cathode and a yolk–shell structured FS@NC anode, and the results showed superior energy storage performance.